The servant leadership and its impact in organizational trust An analytical study in oil products distribution company / Baghdad - سعيد هديل كاظم; عبد نور باسم (Journal of Economics and Administrative Sciences, 2019)
Abstract The research aims at the relationship between Servant leadership dimensions test as an independent variable and an organizational trust as a variable dependent. Thus it was necessary to answer the following question: Is there a correlation relationship and impact between Servant leadership dimensions and organizational trust? To investigate the contents of the answer, the researcher selected a group of employees in Oil Products Distribution Company / Baghdad. The researcher adopted the analytical descriptive approach in completing his research which dealt with a random sample of (190) individuals representing the research society out of the total number of (376) person from the middle and high Leaders. Depending on questionnaire form included (39) items, (240) of which was valid for statistical analysis, as well as conducting interviews as a tool for collecting data which analyzed the adoption of statistical software (Spss V.21, Amos V.18) was used with statistical methods (R²), Percentage, Tolerance Analysis, Torsional and Flattening Scale, Mono-Contrast Analysis, Alpha Cranach and Celt Brown for Half-Spacing, KMO and Bartlett`s Test, analysis of total variance of dimensional roots, to test the hypotheses. The study found the group’s conclusions including: a relationship directly and the impact of Servant leadership dimensions direct impact on the organizational trust.